Developing the Research Issues by Integrating Based On the Four Noble Truths - Karnjanapokin, Korneak (Asia Pacific Journal of Religions and Cultures, 2020)
This article introduces the guideline to analyze a research issue and a research proposition which is an important step for the research. If the problem analysis is a mistake or deviate from the truth and has no direction. It is difficult to develop a research project that can lead to a solid operation. The guideline to conclude research issues which were introduced was “Developing the research issue by integrating based on the Four Noble Truths of the Buddhism.